Extreme value models in a conditional duration intensity framework - Rodrigo Herrera; Bernhard Schipp (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
The analysis of return series from financial markets is often based on the Peaks-over-threshold (POT) model. This model assumes independent and identically distributed observations and therefore a Poisson process is used to characterize the occurrence of extreme events. However, stylized facts such as clustered extremes and serial dependence typically violate the assumption of independence. In this paper we concentrate on an alternative approach to overcome these difficulties. We consider the stochastic intensity of the point process of exceedances over a threshold in the framework of irregularly spaced data. The main idea is to model the time between exceedances through an Autoregressive Conditional Duration (ACD) model, while the marks are still being modelled by generalized Pareto distributions. The main advantage of this approach is its capability to capture the short-term behaviour of extremes without involving an arbitrary stochastic volatility model or a prefiltration of the data, which certainly impacts the estimation. We make use of the proposed model to obtain an improved estimate for the Value at Risk. The model is then applied and illustrated to transactions data from Bayer AG, a blue chip stock from the German stock market index DAX.
Keywords: C22; C58; F30; 330; extreme value theory; autoregressive conditional duration; value at risk; self-exciting point process; conditional intensity; Risikomaß; Börsenkurs; Extremwerttheorie; Autokorrelation; Statistische Bestandsanalyse; Theorie; Chemieindustrie; Schätzung; Deutschland